How do we reconcile the seemingly contradictory theories of Gestalt language processing and weak central coherence? - Schwartz, Anna M.; Caldwell-Harris, Catherine L. (Frontiers in Psychiatry, 2025)
A long-standing characterization of autistic cognition is variously referred to as detail-oriented, local processing bias, bottom-up processing, and weak central coherence. A related construct, enhanced perceptual functioning, is a mechanism that could account for autistics’ superiority at a variety of detail-oriented visual tasks. However, detail-focused and enhanced perceptual functioning appear the opposite of what is called Gestalt language processing. Observed in autistic language acquisition, whole phrases are produced at the beginning of language learning, rather than the expected smaller unit of single words. This idea has been enlarged to encompass Gestalt processing as a broad cognitive style, said to be characteristic of autistic processing in some cases or for some individuals. We explain and critique these diverse accounts, noting which aspects of them are controversial. We propose a spectrum of reconciliations, beginning with how both attention to detail and production of holistic speech can emerge from enhanced perceptual function. Inherent differences between auditory and visual processing allow holistic processing to be more easily observed in language than in vision. Autistic individuals may less easily learn what level and type of detail correspond to their culture’s normative expectations.